Endoparasite and Microbial Burden in Quail Farm Systems: A Biosecurity and Water Quality Assessment in Central Java, Indonesia - Murwani, R.; Dewi, B. P. A.; Anggraeni, R.; Mulyono, M.; Ambariyanto, A. (Tropical Animal Science Journal, 2025)
Quail farming is vital for smallholder farmers in Central Java, Indonesia; however, productivity often declines due to poor biosecurity, inadequate water quality, and parasitic infections. This study aims to examine biosecurity practices, water quality, and endoparasite loads in ten quail farms (L1-L10) located in Semarang City and nearby regencies. Data were collected through observations, interviews, water sampling, and analysis of quail droppings. Biosecurity scores (maximum 18) were categorized into three groups: Group-1 (scores 13-18), Group-2 (scores 7-12), and Group-3 (scores 1-6). Water quality was assessed based on pH, E. coli, and coliform counts using triplicate samples from each site. The biosecurity score showed that three farms are in Group-1 (L1, L7, L9), five are in Group-2, and two are in Group-3 (L8, L10). The water pH ranged from 4.8 to 8.0; the highest E. coli count was 19.33 CFU/mL (L9), and the highest Coliform count was 89.67 CFU/mL (L5). L1 had the highest parasite load, with Coccidia, Strongyloides, and Ascaridia sp. at 1000 oocysts/g (OPG), 100 OPG, and 33.33 OPG, respectively. Meanwhile, L7 showed no endoparasites or water contamination. Egg production ranged from 64.29% to 90.00%. Although no significant differences in endoparasite prevalence were found among biosecurity groups or water quality (p>0.05), Coliform levels differed significantly (p